2017
DOI: 10.1194/jlr.m077305
|View full text |Cite
|
Sign up to set email alerts
|

An allene oxide and 12-oxophytodienoic acid are key intermediates in jasmonic acid biosynthesis by Fusarium oxysporum

Abstract: Fungi can produce jasmonic acid (JA) and its isoleucine conjugate in large quantities, but little is known about the biosynthesis. Plants form JA from 18:3-3 by 13-lipoxygenase (LOX), allene oxide synthase, and allene oxide cyclase. Shaking cultures of f. sp. released over 200 mg of jasmonates per liter. Nitrogen powder of the mycelia expressed 10-dioxygenase-epoxy alcohol synthase activities, which was confirmed by comparison with the recombinant enzyme. The 13-LOX of could not be detected in the cell-free pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 52 publications
3
32
0
Order By: Relevance
“…Previous work has shown that JA biosynthesis of F. oxysporum is influenced by the growth conditions (Cole et al, ; Oliw and Hamberg, ). Comparison of the expression of CYP mRNA of F. oxysporum under growth in Czapec‐DOX broth under light (with low JA‐Ile biosynthesis) with the expression in PDB in the dark (with high biosynthesis) might indicate potential 13 S ‐AOS candidates (Oliw and Hamberg, ). Whether expressed sequence tags of mRNA could provide this information might be worth further investigations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous work has shown that JA biosynthesis of F. oxysporum is influenced by the growth conditions (Cole et al, ; Oliw and Hamberg, ). Comparison of the expression of CYP mRNA of F. oxysporum under growth in Czapec‐DOX broth under light (with low JA‐Ile biosynthesis) with the expression in PDB in the dark (with high biosynthesis) might indicate potential 13 S ‐AOS candidates (Oliw and Hamberg, ). Whether expressed sequence tags of mRNA could provide this information might be worth further investigations.…”
Section: Discussionmentioning
confidence: 99%
“…Fig. b) (Oliw and Hamberg, ). This observation lends further support for a tightly controlled process from 18:2n‐6 and 18:3n‐3 to the jasmonate end products.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Allene oxides can be formed in plants and fungi from 9‐ and 13‐hydroperoxy metabolites of 18:2 n ‐6 and 18:3 n ‐3 (Hamberg, ; Oliw & Hamberg, ; Vick & Zimmerman, ). Of particular biological significance is the biosynthesis of jasmonic acid.…”
Section: Discussionmentioning
confidence: 99%